Gangguan TMJ pada Penderita Maloklusi: Pemeriksaan dan Hubungannya dengan Perawatan Ortodontik - Permana Irmansyah Masbirin (Faculty of Dentistry, Universitas Indonesia, 2015)
Many researchers had worked on TMD or CMD studies for the last 20 years, but the symptom remains unanswered to lead us into complete treatment. Orthodontic treatment is one of the non-invasive treatment carefully considered by the clinical to cure the TMD. The TMJ is the hinge that connects two main parts of human skull, the cranium and the mandible, through an articular disc that act as shock absorbers and prevent friction of the two. TMJ disorder usually causes unexplained and persistent facial pain in variety degrees, and a constellation of symptoms all related to the dysfunction of the TMJ. Generally, TMD patients present with a number of diagnoses within the TMD category and clinicians should understand each problem carefully. A clinician who believes that TMD is occlusion-related will treat the occlusion to eliminate the problem.